2020
DOI: 10.1111/pan.14008
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia management of laser photocoagulation for retinopathy of prematurity. A retrospective review of perioperative adverse events

Abstract: Aims: The aim of this study was to report the incidence of perioperative adverse events occurring in infants undergoing diode laser photocoagulation of retinopathy of prematurity and to identify clinical risk factors that may affect the incidence. Methods: This was a retrospective study of anesthetic and medical records of premature infants who were treated in the neonatal intensive care unit or an operating theater with laser photocoagulation in our institution between January 2014 and December 2019. Infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Infants undergoing laser treatment have been found to be at high risk of intraoperative and postoperative adverse events like hypotension, bradycardia and apnoea. 33 Repeated anaesthetic procedures may affect the infants' neurodevelopment, and there are concerns about the long-term effects of anti-VEGF treatment on neurodevelopmental outcome. 34 Thus, it is crucial that the ROP screening and treatment procedures are as efficient and gentle as possible, especially as several authors have stressed that ROP is a biomarker for brain volumes at term and later neurodevelopmental outcomes.…”
Section: Centre and Treatment Modalitymentioning
confidence: 99%
“…Infants undergoing laser treatment have been found to be at high risk of intraoperative and postoperative adverse events like hypotension, bradycardia and apnoea. 33 Repeated anaesthetic procedures may affect the infants' neurodevelopment, and there are concerns about the long-term effects of anti-VEGF treatment on neurodevelopmental outcome. 34 Thus, it is crucial that the ROP screening and treatment procedures are as efficient and gentle as possible, especially as several authors have stressed that ROP is a biomarker for brain volumes at term and later neurodevelopmental outcomes.…”
Section: Centre and Treatment Modalitymentioning
confidence: 99%
“…Apart from postoperative apnea and hypoventilation, one of the reservations about the use of opioids and muscle relaxants is prolonged intubation times. In a study in which all infants were intubated with sevoflurane, opioids and muscle relaxants, only 19.4% of the infants could be extubated at the end of the procedure and 40.3% continued mechanical ventilation after 24 hours (23). In 71 cases reported by Nath, LMA was placed in all infants using only sevoflurane and only one infant needed postoperative ventilation, and two infants developed postoperative apnea and bradycardia (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, it carries moderate rates of intraoperative hypotension and postextubation apnea. [ 79 80 ] Likewise, for aggressive ROP requiring vitrectomy, studies have shown that half of the patients were successfully extubated in the operating room, no postoperative complications were observed, and that early vitrectomy is effective despite the perioperative risks. [ 81 ]…”
Section: R Etinopathy Of P Rematurity ...mentioning
confidence: 99%
“…[ 82 ] A summary of reviewed GA studies during ROP treatment is shown in Table 7 . [ 8 9 16 59 76 79 80 81 82 83 84 85 86 87 88 ]…”
Section: R Etinopathy Of P Rematurity ...mentioning
confidence: 99%